2016
DOI: 10.1016/j.jog.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Mantle earthquakes beneath the South Iberia continental margin and Gulf of Cadiz – constraints from an onshore-offshore seismological network

Abstract: The Gulf of Cadiz and the passive continental margin of southern Iberia to the west of the Strait of Gibraltar locally accommodate the presently ongoing convergence between Africa and Eurasia by widespread, rather diffusive, seismic activity. Seismicity of the northern Gulf of Cadiz was derived from an amphibious seismological network, including 24 temporary marine offshore stations, besides the permanent networks in Portugal, Spain, and Morocco. During the 6 month of the offshore network operation, in total 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 79 publications
0
18
0
Order By: Relevance
“…This seems at odds with the necking model we propose in this paper. However, considering these earthquakes are all at shallower depths relative to the rest of the events and that intermediate-depth seismicity has been reported even farther west (Domingues et al, 2013;Geissler et al, 2010;Grevemeyer et al, 2016;Gutscher et al, 2009;Monna et al, 2013), these events likely lie in the mantle lithosphere of Atlantic plate.…”
Section: 1029/2019jb017896mentioning
confidence: 94%
“…This seems at odds with the necking model we propose in this paper. However, considering these earthquakes are all at shallower depths relative to the rest of the events and that intermediate-depth seismicity has been reported even farther west (Domingues et al, 2013;Geissler et al, 2010;Grevemeyer et al, 2016;Gutscher et al, 2009;Monna et al, 2013), these events likely lie in the mantle lithosphere of Atlantic plate.…”
Section: 1029/2019jb017896mentioning
confidence: 94%
“…In offshore SW Iberia, the source area for the large 1755 and 1969 magnitude earthquakes ( Fig. 1a), seismicity relocated by Ocean Bottom Seismometers (OBS) has shown that most of the small magnitude events are occurring at mantle depths, down to 50 km focal depths, again without a clear relationship with the known active tectonic features identified by geological and geophysical surveys (Geissler et al, 2010, Grevemeyer et al, 2016, Silva et al, 2017.…”
Section: Geodynamic Settingmentioning
confidence: 99%
“…The SW Iberia‐Gulf of Cadiz segment of the plate boundary is characterized by a WNW‐ESE oblique dextral convergence between Africa (Nubia plate) and Eurasia (Iberia block) of 4–5 mm/yr [ Fernandes et al ., ; Stich et al ., ; Nocquet , ]. The strain is accommodated by moderate‐ to large‐magnitude earthquakes at shallow to intermediate depths, up to 60 km, most of them clustering along lineations with preferred orientation of NNE‐SSW and WNW‐ESE [ Buforn et al ., ; Stich et al ., ; Geissler et al ., ; Custódio et al ., ; Grevemeyer et al , ], which mostly coincide with segments of thrust and strike‐slip faults and sometimes localize at fault intersections [ Rosas et al ., ]. An important cluster in south Portugal trends ENE‐WSW, along the Cadiz fault, possibly accommodating perpendicular shortening by thrusting and right‐lateral tectonics [ Duarte et al ., , ].…”
Section: Tectonic Settingmentioning
confidence: 99%